Female Genital Cutting and Hepatitis C Spread in Egypt. (7th May 2013) - Kenyon, Chris; Buyze, Jozefien; Apers, Ludwig; Colebunders, Robert
Abstract : A recent analysis of Egypt's first nationally representative survey of hepatitis C virus (HCV) infection found female genital cutting (FGC) to be an independent risk factor for HCV infection for women in urban areas. We use the same dataset to extend this analysis. In an ecological analysis, we find a strong association between FGC and HCV prevalence (PearsonR 2 —74%; P < 0.0001 ). HCV prevalence is significantly higher if FGC is performed by a non-Doctor (15.4%) than a Doctor (4.2%;P < 0.001 ), and the calculated population attributable fraction of FGC for prevalent HCV seropositivity is high in women (79.8%).